2003
DOI: 10.1152/japplphysiol.00806.2002
|View full text |Cite
|
Sign up to set email alerts
|

Temporal coordination of pharyngeal and laryngeal dynamics with breathing during swallowing: single liquid swallows

Abstract: . Temporal coordination of pharyngeal and laryngeal dynamics with breathing during swallowing: single liquid swallows. J Appl Physiol 94: 1735-1743, 2003. First published December 27, 2002 10.1152/japplphysiol.00806.2002The critical integration of timing and patterning between respiratory and swallowing events was studied with simultaneous videofluoroscopic and respiratory recording during single liquid swallows. Respiratory phase patterns and the onsets and durations of 12 predetermined swallowing events and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
167
2
11

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 171 publications
(202 citation statements)
references
References 32 publications
22
167
2
11
Order By: Relevance
“…Another study was developed to described the characteristics of the dysphagia in palliative care patients with malign conditions but without a diagnosis of head and neck cancer. The results supported the hypothesis that patients suffering from cancer that does not affect the head and neck equally present the risk of developing oropharyngeal dysphagia symptoms (21) . Despite the existence of these studies, no bibliographic support was found that distinguished between difficulties to swallow liquid and solid foods in palliative care patients.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Another study was developed to described the characteristics of the dysphagia in palliative care patients with malign conditions but without a diagnosis of head and neck cancer. The results supported the hypothesis that patients suffering from cancer that does not affect the head and neck equally present the risk of developing oropharyngeal dysphagia symptoms (21) . Despite the existence of these studies, no bibliographic support was found that distinguished between difficulties to swallow liquid and solid foods in palliative care patients.…”
Section: Discussionsupporting
confidence: 82%
“…Another study was developed to verify the most prevalent symptoms in the last six months of life for head and neck cancer patients. Among the 93 patients who participated in the study, 45% presented dysphagia, the second most frequent symptom, preceded by pain (21) . Another study was developed to described the characteristics of the dysphagia in palliative care patients with malign conditions but without a diagnosis of head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…São inúmeros os trabalhos a respeito da anatomia e fisiologia da deglutição em idosos saudáveis, evidenciando os sinais provenientes da deglutição senescente (4,37,38,39,40,41,42,43) .…”
Section: R Re Ev VI Is Sã ãO O D Da a L Li It Te Er Ra At Tu Ur Ra A 21unclassified
“…Therefore, four possible respiratory patterns during swallowing have been documented across normal and dysphagia patients, including: expiration-expiration [E-E], expiration-inspiration [E-I], inspiration-expiration [I-E], and inspiration-inspiration [I-I]. With normal adults, the E-E pattern dominates during a swallow (Martin-Harris et al, 2005;Martin-Harris, Brodsky, Price, Michel, & Walters, 2003), meaning air flows out of the system before and after a swallow. Studies with anaesthetized (Doty & Bosma, 1956) or decerebrated (Dick, Oku, Romaniuk, & Cherniack, 1993) cats have reported that the E-E phase predominates during swallowing.…”
Section: Swallowing and Respiratory Patterns Following Hnc Treatmentmentioning
confidence: 99%
“…The use of these devices would have provided further objective confirmation of respiratory activity, as activation of the diaphragm is also associated with activities other than eupneic respirations (e.g., hiccups, schluckatmung, and cough). Airflow measures also allow for duration measurements of obligate pauses in respiration during swallowing, referred to clinically as apnea or 37 respiratory pauses (Martin-Harris et al, 2005;Martin-Harris et al, 2003;Wang et al, 2015). Multiple studies have used plethysmography and/or airflow directional readings in combination with videofluoroscopic recordings to determine swallow-breathing patterns (Martin-Harris et al, 2005;Martin-Harris et al, 2003), permitting direct visual confirmation of swallowing versus indirect confirmation via EMG data.…”
Section: Limitationsmentioning
confidence: 99%